Female fighters of Islamic state : why more from the West? - Sara Mahmood (2015)
The self-styled Islamic State’s (IS) conception of a caliphate, which accords women a significant role in building and sustaining a state, has mobilised a large number of female supporters and sympathisers to Iraq and Syria from the West. Why is this so?